Fast and sensitive immuno-PCR assisted by plasmonic magnetic nanoparticles. (June 2021) - Qiu, Yuwei; Jiang, Kunlun; Wu, Jingrui; Mi, Hua; Peng, Yung-Kang; Go, Yun Young; Park, Hyun June; Lee, Jung-Hoon
Highlights: Ultrafast PPT-iPCR assay based on dual-functional plasmonic magnetic nanoparticles (Fe3 O4 @Au) was achieved within 8 min. Fast, energy-efficient and inexpensive PPT-iPCR assay with high sensitivity and selectivity was realized for TNF-α detection. The detection limit of PPT-iPCR was 1.30 fg/mL, which was 3 orders of magnitude lower than that of commercial kits. PPT-iPCR allowed the use of existing ELISA/PCR protocols, making them suitable for immediate use in clinical applications. Abstract: Immunoassay for quantitative protein detection is an important tool in biomedical and clinical researches. Various types of detection platforms have emerged from typical ELISA using chromogenic reporter to more advanced approaches including electric, electrochemiluminescent and fluorogenic reporters to create quantitative analysis. Among them, fluorescence-based immuno-polymerase chain reaction (iPCR) is regarded as one of the simplest and most sensitive strategy that combines the specificity of immunological recognition technology with the amplification power of PCR. However, most PCR-based immunoassays to date have relied on the costly and time-consuming Peltier block heating technology. Here, we introduce a plasmonic photothermal (PPT)-iPCR assay method based on plasmonic magnetic nanoparticles to reduce the required thermal cycling time of amplification without compromising the superior sensitivity of iPCR. PPT-iPCR is capable of sensitive and quantitative detection of tumor necrosis factor-α (TNF-α) proteins ranging from 0.1 pg/mL to 1000 pg/mL within 8 min. PPT-iPCR uses fast, energy-efficient and inexpensive LED-based devices and can be used with commercial kits without modification while achieving excellent sensitivity. Our strategy can be easily combined with mobile phones or micro-optics, thus laying the foundation for the development of inexpensive, highly mobile detection devices that can quickly and accurately analyze biomarkers in a variety of diagnostic applications. Graphical abstract: Image, graphical abstract